Harmonic Mitigation for Non-Linear Load using TSH Active Power Filter with PID Controller - Garima Sinha; Pankaj kumar Goswami; Sudhir kr. Sharma (International Journal of Applied Power Engineering (IJAPE), 2018)
Electronic equipments, widely used in present living era, required to have improved power quality. When such type of equipments are connected to electric supply distribution system, they introduce non sinusoidal effect in the line current because of their non-linear relationship in voltage and current. Moreover, harmonics in the line current are also produced. With constantly growing imploration of such type of nonlinear equipments at a large scale, harmonic distortions in line current have become a significant crunch. This required some methods involving the reduction of harmonics in the line current as well as Power Factor Improvement/Correction. The primary goal of this proposed work is to reduce the harmonics produced in line current and to improve power quality of non-linear load by designing a converter with parallel processing scheme, named TSH Active power filter (Transformer less shunt active power filter) with PID controller. Here a separate dc source is employed to supply the shunt connected converter, a voltage source inverter, to remove the requirement of bulky transformer at supply end. This paper depicted the process of reduction of total harmonic distortion (THD), generated due to nonlinear characteristics of load and power factor improvement by shunt compensation. The proposed designs are modeled and simukated using Matlab simulation software.